Bioecological Characteristics of Cossack Juniper (Juniperus Sabina) in Kazakhstan - Abdikarimova, P.U.; Kali, A.; Shorin, S.S.; Beisenova, R.; Rakhymzhan, Zh.; Nugmanov, A.; Myrzagaliyeva, A. (International Journal of Design & Nature and Ecodynamics, 2024)
The work assessed the bioecological characteristics of the rare species Juniperus sabina in Kazakhstan. The significance of the research is that it provides knowledge about the morphological and adaptive characteristics of juniper. The purpose of the research is to study the morphoanatomical features of the vegetative organs of Cossack juniper in the Karaganda and Ulytau regions. Samples were selected from Karaganda, Zhanaarkinsky, Karkaraly and Ulytau regions. The following indicators were determined: juniper length and width, height and thickness; length of annual growth of shoots, cross-sectional area, size of the vascular bundle, average diameter of the receptacle, width of the epidermis; size of the conductive bundle. As a result, it was established that Cossack juniper (Juniperus sabina) has a low level of variability in the morphological parameters of vegetative organs. The growth of individuals was observed in the populations of the Ulytau and Karkaraly regions, although the development of subcutaneous tissue was not so great. And in the populations of Cossack juniper in the Zhanaarka region, subcutaneous tissue, cuticle and epidermis are developed. This reflects the adaptation of plants to growing conditions in arid regions. The results make it possible to organize measures to protect juniper as a rare species.
Keywords: Cossack juniper; morphological variability; anatomical features; environmental adaptation; Kazakhstan